2015
DOI: 10.1111/irv.12351
|View full text |Cite
|
Sign up to set email alerts
|

A review of the changes to the licensing of influenza vaccines in Europe

Abstract: In 2014, the European Committee for Medicinal Products for Human Use (CHMP) published a draft regulatory guideline for the evaluation of influenza vaccines. Following a public consultation round, the final guidance will be published in the near future. Here, we highlight the main changes in the clinical section in this guideline and discuss the background to these changes and whether the new consolidated guidance document can be expected to achieve a better understanding of the performance of seasonal, zoonoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 26 publications
0
55
0
3
Order By: Relevance
“…Currently, there are no established correlates of protection for young age groups in all the three assays. Nevertheless, the new CHMP guideline has abolished the traditional criteria with the recognition that relying on these criteria of measuring protective effectiveness might not be appropriate for various situations and this opens the opportunities to advance the field on correlates of protection in various subpopulations against different influenza strains …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, there are no established correlates of protection for young age groups in all the three assays. Nevertheless, the new CHMP guideline has abolished the traditional criteria with the recognition that relying on these criteria of measuring protective effectiveness might not be appropriate for various situations and this opens the opportunities to advance the field on correlates of protection in various subpopulations against different influenza strains …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the new CHMP guideline has abolished the traditional criteria with the recognition that relying on these criteria of measuring protective effectiveness might not be appropriate for various situations and this opens the opportunities to advance the field on correlates of protection in various subpopulations against different influenza strains. 9 Another key finding was that SRH appears to have the worst correlation with protection against influenza H3N2, as the estimates of protective efficacy fluctuated when the cut-off SRH values increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse experiments showed that MF59 stimulates the local inflammatory response at the injection site and thus increases the uptake of antigen by activated dendritic cells 43 . Similarly, AS03 facilities a stronger antibody response by inducing a local cytokine and chemokine response at the injection site to enhance antigen uptake 43 .…”
Section: Articlementioning
confidence: 99%